2016
DOI: 10.1093/geront/gnw050
|View full text |Cite
|
Sign up to set email alerts
|

The Associations and Correlations Between Self-reported Health and Neighborhood Cohesion and Disorder in a Community-dwelling U.S. Chinese Population

Abstract: Our findings suggest that neighborhood cohesion and neighborhood disorder are correlated to the health of U.S. Chinese older adults. Future longitudinal research should examine the relationship between community characteristics, both structural and social, and health-related outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 51 publications
(51 reference statements)
1
27
0
Order By: Relevance
“…Although no significant associations were found between neighborhood cohesion and hoarding, unsanitary conditions, and inadequate utilities, the lack of associations implied the complexity of the relationship between neighborhood characteristics and self‐neglect in this Chinese community. A prior study found that, in this Chinese community, neighborhood cohesion was positively correlated with neighborhood disorder . In other words, greater neighborhood cohesion may predict greater neighborhood disorder in the same community.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Although no significant associations were found between neighborhood cohesion and hoarding, unsanitary conditions, and inadequate utilities, the lack of associations implied the complexity of the relationship between neighborhood characteristics and self‐neglect in this Chinese community. A prior study found that, in this Chinese community, neighborhood cohesion was positively correlated with neighborhood disorder . In other words, greater neighborhood cohesion may predict greater neighborhood disorder in the same community.…”
Section: Discussionmentioning
confidence: 65%
“…A prior study found that, in this Chinese community, neighborhood cohesion was positively correlated with neighborhood disorder. 21 In other words, greater neighborhood cohesion may predict greater neighborhood disorder in the same community. Moreover, neighborhood disorder has been linked to adverse health outcomes, which may increase the risk of self-neglect.…”
Section: Discussionmentioning
confidence: 99%
“…A possibility is that most Chinese older adults live in Chinatown or other ethnic enclaves in which other Chinese people reside. This type of coethnic residence pattern, in which residents are of the same ethnic background, usually exists in working‐class neighborhoods that are not well maintained . On the other hand, the high coethnic density could also promote a higher level of social engagement.…”
Section: Discussionmentioning
confidence: 99%
“…Neighborhood disorder and cohesion was measured by a list of questions used in previous research . Each neighborhood disorder question was measured on a 4‐point scale (from 0 [never] to 3 [often]) regarding the frequency of observed presence of neighborhood disorganization, such as trash, strangers, or unsafety of walking around.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation